KEBIJAKAN PENGELOLAAN BARANG MILIK DAERAH DI KABUPATEN LAMPUNG UTARA - Sriyani; Arifah Fibri Andriani; Ria Dewi Ambarwati (Journal Publicuho, 2025)
The purpose of this study is to evaluate the implementation of regional asset management in the North Lampung Regency,  identify the strengths and weaknesses of regional asset management in the North Lampung Regency Government, and develop strategies for optimising regional asset management in North Lampung. This research is a qualitative study with a descriptive approach. Based on the results of the analysis conducted on the management of Regional Assets (BMD) in North Lampung Regency, overall BMD management is in the "fairly Good" criteria with a rating of 78.45% of the criteria scale or 3.92 (Likert scale 5). However, BMD management in North Lampung Regency still requires improvement, especially in several aspects that are still in the "Less Good" criteria, such as the inventory process and utilisation of BMD.